Preadolescent Girls and the Presentation of Self: A Dramaturgical Perspective - Moore, Lori; MacKinnon, David (Alberta Journal of Educational Research, 2001)
The purpose of this study was to examine how five preadolescent girls constructed and presented their social identities and the perceived influence of the media in this process. A series of individual and focus group interviews were held with five 9- and 10-year-old girls. Goffman's (1959) interactionist perspective of the theatrical performance provided the framework for the inquiry. The participants in the study offered testimonials that clearly indicate the power and influence of the media in manipulating young girls' perceptions of themselves and others.